Efficient Background-Noise-Reduced Single-Mode Waveguides Platform for On-Chip Integrated Photonics - Yevhenii Morozov; Anatoly Lapchuk; Zichun Le; Ye-Fei Dong (IEEE Photonics Journal, 2019)
In this paper, we propose a modified platform for on-chip integrated photonics. The platform allows one to efficiently connect a tapered optical fiber or fiber lens to an on-chip waveguide with high alignment precision and to mechanically fix the fiber on the chip to prevent defocusing, lateral shift, and angular detuning during device operation. The metal screen of the connector—made of gold—prevents any penetration of the background radiation into the optical circuit, something which is not possible to achieve in all the cases using tapers or grating couplers. We performed impedance-matching analysis based on transmission line theory and numerically optimized the platform, allowing us to achieve a tapered fiber mode to on-chip waveguide mode transformation efficiency as high as 96% (−0.177 dB) at wavelengths of 785 and 1550 nm. The platform bandwidth (transformation efficiency ≥80%) is 151 nm. At the same time, transformation efficiency is stable (reduction less than 1%) in an offset range of ±2 nm—enough for modern on-chip and off-chip coherent light sources. The horizontal and vertical lateral alignment tolerances for the platform are 700 and 600 nm, respectively, at a transformation efficiency ≥80% while the longitudinal alignment tolerance is approximately 70 nm. Due to the relatively high lateral and longitudinal tolerances, it is possible to produce the platform at high efficiency using existing fabrication nanotechnologies. We believe that this platform accelerates the realization of fully on-chip Raman spectroscopes and may be of practical importance in other on-chip integrated photonic devices.